Uma contribuição da área da inteligência artificial na análise da qualidade da energia elétrica - Martins, Ronan Marcelo (1999)
The use of capacitors for correcting the power factor is a very well known approach in industry. However, the increase of harmonic sources in power Systems is heightening the risk of resonance and, consequently, a drastic decrease in electric power quality. In order to keep the rating voltage, the power factor, and the voltage and current harmonic distortions within acceptable limits, a Expert System using Fuzzy Logic for resolving conflicts of rules was developed. This approach is able to decide about the optimal distribution of the capacitor banks, and when necessary, decides on the use of fílters for harmonic compensation, indicating the best fílter and the corresponding tuning ffequency. The decisions are based on the rating voltage, the power factor, and the whole voltage and current harmonic distortions.